PREVALENCE OF CELIAC DISEASE PREDISPOSING GENOTYPES, INCLUDING HLA-DQ2.2 VARIANT, IN BRAZILIAN CHILDREN - SELLESKI,Nicole (2018)
ABSTRACT BACKGROUND: Celiac disease is an autoimmune enteropathy triggered by the ingestion of gluten in genetically susceptible individuals. Almost all celiac patients carry immune recognition genes coding for HLA-DQ2.5 and DQ8 heterodimers. Over the last few years, great importance has been given to HLA-DQ2.2 as probable predisposing variant, although controversies still exist regarding its relevance. OBJECTIVE: The aim of our study was to determine the possible existence of an association between HLA-DQ2.2 and celiac disease in Brazilian children by analyzing the prevalence of the predisposing variants for celiac disease in a representative group of children of a population in which this determination is still missing. METHODS: HLA-DQ typing was performed in samples from a group of celiac (n=100) and non-celiac children (n=110). All samples were tested for the presence of the following variants: DQA1*05-DQB1*02 (DQ2.5), DQA1*03-DQB1*03:02 (DQ8) and DQA1*02:01-DQB1*02:02 (DQ2.2). Fisher`s exact test was used for statistical analysis. RESULTS: In the group of 100 celiac children, 78 (78%) were positive for DQ2, 13 (13 %) were DQ2/DQ8 and 6 (6%) were DQ8 positives. The HLA-DQ pattern in the 110 non-celiac children was as follows: positive for DQ2 in 33 (29.9%) samples, in 2 (1.8 %) was positive for DQ2/DQ8 and in 15 (13.6%) was positive for DQ8. We found significant differences between the distribution of some but not all of the analyzed alleles when comparing celiac and non-celiac children. CONCLUSION: The genotyping of celiac disease HLA-DQ predisposing alleles showed similarities with HLA-DQ patterns found in both European and non-European populations, which may be a reflection of the miscegenation, which gave origin to the current Brazilian population. No significant association was found between DQ2.2 variant and celiac disease in the studied population.